Perbandingan Kinerja Portofolio yang Dibentuk dengan Single Index Model pada Saham-Saham yang Terdaftar dalam Indeks LQ45 dan Kompas 100 Tahun 2018 - Dini Iskandar; Martalena Martalena; Natasha Desiree Julianto (Jurnal Akuntansi)
Stocks as an investment instrument that categorized as a high risk dan high return instrument. Therefore, investors should distributed their invesment funds in a number of shares by forming an optimal portfolio where the highest return is obtain at a certain risk or the lowest risk at certain return. On this study the portfolio forming used the Single Index Model. Portfolio formed from stocks at LQ 45 Index and Kompas 100 Index by aim to get the comparison of their performance.The result of this study indicate that LQ 45 portfolio that containing PTBA, ICBP, BBCA, PGAS and ANTM has a lower return than Kompas 100 portfolio that containing KREN,CPIN, PTBA and JFPA. The performance of both portfolio that analyze by Sharpe Index, Treynor Index and Jensen Index indicate that portfolio of Kompas 100 better than portfolio of LQ 45 , however both of them showed the good performance because their result are positif that mean better than market.